HOUSING POLICY AND HOUSING IN SOCIALIST MACEDONIA (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2020)
Owning a home as a space (apartment or house) is the inalienable right of every individual. Home is the center of the world for everyone who owns it, and its absence causes a number of repercussions in ones social life. Housing is an important context in the political, economic and social life and depends on its conditions. Regulated housing, as part of the social and spatial policy, is a witness of a functioning and developed country, while at the same time contributing to social cohesion, preserved integrity and well-being of each individual. In Yugoslav times, ideological coloration required equality in the ownership and allocation of an apartment; declaring it a personal investment and a social good, the state had the imperative to provide the individual with this good or to create suitable conditions, adapted to the existing standard, to obtain it himself without much inconvenience. Self-management and associated labor introduce mitigating circumstances for the acquisition of housing rights, but also a series of irregularities and inconsistencies in its resolution.
Keywords: home; apartment; housing; socialism; self-management